2016
DOI: 10.4172/2165-784x.1000201
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Technologies for Interdisciplinary Education

Abstract: Integrated applications using Augmented Reality (AR) and Building Information Modeling (BIM), enhanced by the capacity of handheld devices, are becoming prevalent in the building industry; however their use in learning environments has not been fully explored. Recent research shows that interaction with computer-based tools can enhance learning and collaboration skills. Augmented Reality-the ability to enhance real world observations with computer-generated information-is bringing new dimensions to learning. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…During the Renaissance period, many well known architects were engineers, master builders, artists and sculptors. This result with a synthesized art and technology in one building with an integrative practice (Vassigh S, et al, 2011). In the 17th century, the industrial thought began with the theories of Consciousness.…”
Section: Philosophy Of Integrationmentioning
confidence: 97%
“…During the Renaissance period, many well known architects were engineers, master builders, artists and sculptors. This result with a synthesized art and technology in one building with an integrative practice (Vassigh S, et al, 2011). In the 17th century, the industrial thought began with the theories of Consciousness.…”
Section: Philosophy Of Integrationmentioning
confidence: 97%
“…To get these latter groups up to speed in fulfilling the rising worker needs in the construction industry, integrated approaches are highly encouraged; the approach whose principles and subsequent applications are contrary to the unilineal approach used traditionally. Most courses in the universities or schools tend to emphasize a specific field of study and less of interdisciplinary approaches leading to a single learning area like physics or life science (Carrasquillo et al, 2017;Vassigh, 2016). But research has shown that the most sustainable or efficient construction ventures have been achieved through integrated design and construction processes which make this collaborative approach most viable today (Carrasquillo et al, 2017;Vassigh, 2016).…”
Section: Cs-2022-49mentioning
confidence: 99%
“…Most courses in the universities or schools tend to emphasize a specific field of study and less of interdisciplinary approaches leading to a single learning area like physics or life science (Carrasquillo et al, 2017;Vassigh, 2016). But research has shown that the most sustainable or efficient construction ventures have been achieved through integrated design and construction processes which make this collaborative approach most viable today (Carrasquillo et al, 2017;Vassigh, 2016). Collaboration is a relationship that has benefits for the parties involved; usually obtaining results that are greater than the results obtained alone (Wao et al, 2018;Slusarek et al, 2010).…”
Section: Cs-2022-49mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the authors at their current and past institutions have always observed large numbers of unmotivated students who have had very limited chances to learn about advanced technologies that can potentially increase their interests and, therefore, motive them. There have been efforts to increase engagement and interaction in engineering classes through computer-based learning environments via virtual reality (VR) and augmented reality (AR) [12,13,14,15]. Despite their benefits, these prior works have been mostly limited to better visualization of course materials in a passive manner, rather than having interactive components that dynamically involve students in classrooms.…”
Section: Introductionmentioning
confidence: 99%